Chapter 5.4 The Profession of Research Management and Administration in South Africa - Les Labuschagne (Emerald Publishing Limited, 2023)
This chapter outlines the circumstances in South Africa (SA) that led to the evolution of the profession of research management and administration (RMA) in the country. The public higher education (HE) sector has undergone significant change since 1994, and the RMA profession has struggled to keep abreast. However, through its national professional society, SARIMA, a concerted effort is being made to facilitate and advance the RMA pipeline. SARIMA was instrumental in developing the Professional Competency Framework for SA and is now focussed on creating awareness and providing development opportunities for RMAs to meet the requirements. RMA in SA is proliferating as the public HE sector expands in response to growing demands and deliberate interventions by the government.
10.1108/978-1-80382-701-820231037; 10.1108/978-1-80382-701-820231037; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262